PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP NIAT BERWIRAUSAHA YANG DI MEDIASI OLEH MOTIVASI DAN SIKAP PADA MAHASISWA S1 MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA ANGKATAN 2016 - Rizki Fernanda; Ridwan Ibrahim (Departemen Manajemen, 2022)
The purpose of this study is to examine the effect of entrepreneurship education on entrepreneurial intentions mediated by motivation and attitudes in undergraduate students of Management, Faculty of Economics and Business, Syiah Kuala University. This research is a census research using a questionnaire as an instrument. The population in this study were all students of S1 Management Class 2016, Faculty of Economics and Business, Syiah Kuala University, totaling 84 people. The results showed that entrepreneurship education had a positive and significant effect on entrepreneurial intentions. Motivation and attitude have a significant positive relationship on entrepreneurship education and entrepreneurial intention. The mediation test shows the variables of motivation and attitudes to partially mediate the relationship between entrepreneurship education and entrepreneurial intention.